Parent-Child Play and the Emergence of Externalizing and Internalizing Behavior Problems in Childhood: A Systematic Review - Schneider, Mirjam; Falkenberg, Irina; Berger, Philipp (Frontiers in Psychology, 2022)
It has widely been accepted that play has a major role in human development. The play situation is considered a save and controlled space in which children can learn to express their problems and to regulate their emotions, thus promoting emotional and behavioral adjustment. In early childhood, this process is thought to emerge in close interaction with caregivers. Parent-child play is thus viewed as an ideal window for parents to connect with their children and to support them in their social-emotional development. In this preregistered systematic review, we sought to integrate evidence from developmental and clinical psychology to shed more light on the role of parents in the relationship between parent-child play and children’s behavioral adjustment as expressed in internalizing or externalizing behavior. Our review revealed that increased harsh control during play interactions as well as a lack of parental responsiveness, warmth and sensitivity were found to be associated with increased behavioral problems. Yet, no protective effect of warmth or responsiveness could be found in the context of risk groups. Moreover, the included studies indicated that positive affect expressed by parents during parent-child play was associated with fewer behavior problems in children, while negative affect was associated with more behavior problems. In general, this review revealed that quality and quantity of playful parent-child interactions were reduced in children with behavioral problems of both domains compared to children without behavioral problems. These findings illustrate the important role of parental characteristics during play interactions and their possible impact on children’s behavioral adjustment.